Creating the Human: Theological Foundations for a Christian Humanistic Education - Gelpi, Donald L. (Horizons, 1997)
This article explores the contribution which a strictly normative theology of conversion might make to an understanding of Christian humanistic education. The first part of the article argues for the need for an ongoing, multidisciplinary discussion of the nature of the human in order to clarify the goals of humanistic education. Part two argues that the four secular forms of conversion—affective, intellectual, personal moral, and socio-political—set important goals for a balanced, humanistic education. Part three argues that the transvaluation of the secular forms of education effected by Christian conversion defines fundamental aims of Christian humanistic education.